TORREFIED BRIQUETTES OF SUGAR CANE BAGASSE AND EUCALYPTUS - Costa,Emylle Veloso Santos (2019)
ABSTRACT Torrefaction and briquetting are two techniques that improve the quality of the biomass and facilitate direct use as fuel. The objective was to evaluate the effect of torrefaction temperature on the properties of the compound briquettes made from sugar cane bagasse and Eucalyptus sawdust. After sample preparation and particle analyses, briquettes were produced with the mixture of the two biomasses, a total of five compositions (0, 25, 50, 75 and 100%) at 120 °C and pressure of 1500 PSI. Subsequently, the briquettes were torrefied at temperatures of 180, 220 and 260 °C, for a period of 15 minutes. According to the results, both biomasses of Eucalyptus sawdust and sugar cane bagasse showed potential for the production of briquettes. The torrefaction reduced hygroscopicity and increased the calorific value of compound briquettes. The ideal composition for the production of briquettes is 100% Eucalyptus. The composition of 50% Eucalyptus + 50% sugar cane bagasse is also a great option, as some bagasse parameters were excellent. 260 °C was the best temperature to promote energy savings.